IDENTIFICATION OF MEDICINAL PLANTS IN KEBUN RAYA SRIWIJAYA AND RESIDENCY OF BAKUNG VILLAGE, OGAN ILIR DISTRICT - Komalasari, Oom; Maryani, Sri; Juairiyah, Oktaf; Susanto, Tri (Publikasi Penelitian Terapan dan Kebijakan, 2019)
Many types of plants are used by the community as medicinal herbs, but how to use them varies based on local wisdom of the local community. It is necessary to identify medicinal plants in the Sriwijaya Botanical Garden and its usage by the Bakung Village community to increase the collection of the Sriwijaya botanical garden and increase the amount of genetic conservation of medicinal plants in the wetlands. Data collection techniques carried out by field surveys and interviews and data were analyzed descriptively qualitatively. There were 31 types of medicinal plants used by the community in Bakung Village. The leaves are the most widely used and processed by boiling and then drinking the water. The results of the exploration of medicinal plants can add a database of medicinal plants in the Sriwijaya Botanical Garden.